2021
DOI: 10.1053/j.jvca.2020.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Management in Severe Coronavirus Disease 2019 Patients on Extracorporeal Membrane Oxygenation

Abstract: Objective: To explore special coagulation characteristics and anticoagulation management in extracorporeal membrane oxygenation (ECMO)À assisted patients with coronavirus disease 2019 (COVID-19). Design: Single-center, retrospective observation of a series of patients. Participants: Laboratory-confirmed severe COVID-19 patients who received venovenous ECMO support from January 20ÀMay 20, 2020. Interventions: This study analyzed the anticoagulation management and monitoring strategies, bleeding complications, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 35 publications
4
41
1
1
Order By: Relevance
“…aPTT significantly lengthened between day 1 and day 7 only in the COVID-19 group (median difference þ18.1 seconds, p ¼ 0.011). This was related to higher UFH doses in the COVID-19 group (median 38,000 [27,,000] vs. 24,000 [19,,000] IU/24 h, p ¼ 0.0126). Heparin resistance (defined as doses of UFH greater than 35,000 IU/day to raise the target) was observed in 70% of the COVID-19 patients.…”
Section: Conventional Parametersmentioning
confidence: 96%
See 1 more Smart Citation
“…aPTT significantly lengthened between day 1 and day 7 only in the COVID-19 group (median difference þ18.1 seconds, p ¼ 0.011). This was related to higher UFH doses in the COVID-19 group (median 38,000 [27,,000] vs. 24,000 [19,,000] IU/24 h, p ¼ 0.0126). Heparin resistance (defined as doses of UFH greater than 35,000 IU/day to raise the target) was observed in 70% of the COVID-19 patients.…”
Section: Conventional Parametersmentioning
confidence: 96%
“…12,13 Some authors suggested that these bleeding events might result from worsening COVID-19-associated coagulopathy during ECMO support, further leading to disseminated intravascular coagulation, enhanced fibrinolysis or acquired von Willebrand syndrome, or from heparin overdose. 14 However, data on the kinetics of coagulation and fibrinolysis markers over the course of vv-ECMO in COVID-19 patients which might support this hypothesis are scarce [15][16][17][18][19] and direct comparisons with non-COVID-19 patients are lacking.…”
Section: Introductionmentioning
confidence: 99%
“… Bleeding events are observed in 7.8% of patients with COVID-19 infection, which are sensitive to the use of escalated doses of anticoagulants ( 19 ). Point-of-care monitoring of coagulation, including thromboelastography ( 20 ) can be considered to manage hemostasis in the perioperative period. …”
Section: Protection Of the Patientmentioning
confidence: 99%
“…A pulmonary protective ventilator strategy was adopted after ECMO initiation (FiO2 < 40%, tidal volume 2-4 ml/kg, plateau pressure < 25 cmH2O, and respiratory rate 8-10 breaths/min. 33 The anticoagulant heparin unfractionated (UFH) was used for all patients, with a bolus dose of 50 U/kg 10 minutes before cannulation. If the activated clotting time (ACT) is < 180 seconds, the continuous intravenous infusion of UFH is increased at a rate of 2-20 U/kg/hour, with a target ACT of 180-200 seconds and an activated partial thromboplastin time (aPTT) of 50-80 seconds (or 1.5 times the baseline).…”
Section: Ecmo Initiation On Ardsmentioning
confidence: 99%
“…If the activated clotting time (ACT) is < 180 seconds, the continuous intravenous infusion of UFH is increased at a rate of 2-20 U/kg/hour, with a target ACT of 180-200 seconds and an activated partial thromboplastin time (aPTT) of 50-80 seconds (or 1.5 times the baseline). 33 Figure 6 shows a flowchart of ECMO initiation on ARDS. while in patients using ECMO-VV, there is no recovery of lung function after 2-3 weeks.…”
Section: Ecmo Initiation On Ardsmentioning
confidence: 99%